Exposição a agrotóxicos em trabalhadores rurais da região central no Rio Grande do Sul - Brondani, Vivian de Franceschi (2023)
Introduction: the implementation of agrochemicals has boosted agricultural productivity, while the populations and rural workers have been exposed to the risks of these compounds. Studies have established an epidemiological association between exposure to pesticides and high rates of chronic diseases. Both pesticides and chronic non-communicable diseases are configured as priorities in health research. Objective: analyze the exposure to pesticides among rural workers, describing self-reported chronic diseases. Method: this is an observational, analytical and cross-sectional epidemiological study. It was carried out with 36 small rural grain producers from cities in the central region of Rio Grande do Sul. The participants were selected by convenience. Data collection took place in two stages, carried out at the participant's home. The first was an interview, and the second was the collection of biological material, blood. The blood samples were collected by puncture in peripheral veins with needle and syringe, a total volume of 10ml, and after being prepared for biochemical analysis, the values of the enzymes acetylcholinesterase and butyrylcholinesterase were analyzed to assess the levels of pesticide intoxication. Pesticide residues present in the participants were also analyzed. The study was approved by the Research Ethics Committee of the Federal University of Santa Maria under opinion nº 3.800.196. Results: most of the participants were men, with schooling ranging from 6 to 9 years, and all have or had contact with pesticides. The main grain crop observed was rice, on land owned by the workers themselves, and because they were small producers, most of them handled pesticides an average of 100 hours a year. The most frequent self-reported chronic diseases were hypertension and diabetes mellitus, and all of those who reported them underwent treatment for the disease. High values for acetylcholinesterase and butyrylcholinesterase were observed, but some participants showed inhibition of the enzymes, indicating intoxication. This fact was corroborated by the analysis of compounds present in serum and plasma of the participants, in which 38 types of toxic compounds were detected. Conclusion: the analysis of pesticides in serum and plasma indicated the occurrence of several pesticides and some metabolites indicating the need for a more comprehensive study. The multifactoriality of chronic diseases makes it impossible to say whether the developed pathology is directly related to the agrochemical, but it may be included as a predisposing risk factor.